Case-Based Curriculum for Pediatric Residents in Diabetes Fundamentals - Iman Al-Gadi; Stephanie Sisley (Association of American Medical Colleges, 2021)
Introduction Pediatricians are at the front line to diagnose new-onset diabetes and treat acute diabetes complications in children. Pediatric residents need a strong foundation in recognizing and managing pediatric diabetes, imposing a demand for a structured, comprehensive pediatric-specific diabetes curriculum. Methods This three-module case-based curriculum focused on diabetes fundamentals relevant to pediatricians in the outpatient and inpatient settings. Each module covered an independent topic within pediatric diabetes. Topics included diabetic ketoacidosis, new-onset diabetes management, and acute complications of diabetes. The modules were focused, short, and flexible to accommodate learners' demanding clinical duties and time limitations. We delivered the curriculum to pediatric residents rotating in the inpatient endocrinology department over 3 separate days. Pre- and posttests assessed learners' knowledge and confidence in diabetes care. Results We tested the curriculum for 7 months in 10 individual cycles, with 11 learners participating. We noted an increase in learners' scores on diabetes knowledge assessment of 16% (95% CI, 5-28; p = .01) after completing the curriculum. The residents' confidence in performing diabetes clinical care skills also improved, with the majority going from reporting low or neutral confidence before instruction to reporting high confidence after instruction. Learners reported 100% extreme satisfaction with the curriculum. Discussion This case-based curriculum exposed residents to pediatric diabetes using authentic, clinically relevant, engaging scenarios. The curriculum enabled learners to actively rationalize their thought process and slow down learning. Short and focused, the curriculum was suitable for mitigating the cognitive load and the time constraints in busy clinical environments.